Assessing the need and potential of assisted migration using species distribution models. (April 2016) - Hällfors, M.H.; Aikio, S.; Fronzek, S.; Hellmann, J.J.; Ryttäri, T.; Heikkinen, R.K.
Abstract: Assisted migration (AM) has been suggested as a management strategy for aiding species in reaching newly suitable locations as climate changes. Species distribution models (SDMs) can provide important insights for decisions on whether to assist a species in its migration; however, their application includes uncertainties. In this study, we use consensus SDMs to model the future suitable areas for 13 vascular plant species with poor dispersal capacity. Based on the outputs of SDMs under different climate change scenarios and future times, we quantify the predicted changes in suitable area by calculating metrics that describe the need and potential for migration. We find that, by the end of the 21st century, one of the species would benefit from AM under mild climate change, seven under moderate change, and for 12 out of 13 species studied AM appears to be a relevant conservation method under strong climate change. We also test the effect of different modeling attributes on the metrics and find little variation between SDMs constructed using different combinations of modeling methods and variable sets. However, the choice of climate variables had a larger influence on the level of the metrics than did the modeling method. We therefore suggest that the choice of climate variables should receive ample attention when measuring climate change threat using SDMs and that experiments aiming to uncover critical environmental factors for individual species should be extensively conducted. This study illustrates that dispersal assistance may be needed for many species under a wide range of possible future climates. Highlights: Species distribution models provide useful insights for assisted migration (AM). Model outputs can be converted into metrics describing the need and potential for AM. Metrics combine losses and gains of suitable areas for a species into one index. Several dispersal-limited species may benefit from AM under strong climate change. Choice of climate variables has a larger effect on metrics than choice of modeling method.